2006
DOI: 10.1093/bja/ael235
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index is a topographically dependent variable in patients receiving propofol anaesthesia

Abstract: The present results provide evidence that BIS index is a topographically dependent variable in patients receiving propofol anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…20 This is in accordance with our study results of a consistent occipital/frontal bias of ϩ10 BIS units. They also found weak frontal-central correlation (r 2 ϭ 0.374) and moderate frontal-parietal correlation (r 2 ϭ 0.66), 20 which was also comparable with our moderate frontal/occipital correlation (r 2 ϭ 0.671) during anesthesia maintenance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…20 This is in accordance with our study results of a consistent occipital/frontal bias of ϩ10 BIS units. They also found weak frontal-central correlation (r 2 ϭ 0.374) and moderate frontal-parietal correlation (r 2 ϭ 0.66), 20 which was also comparable with our moderate frontal/occipital correlation (r 2 ϭ 0.671) during anesthesia maintenance.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Pandin et al 20 demonstrated, in patients receiving graded increases in propofol target controlled infusion, that BIS A-1000 (version 3.12) exhibited consistently central/frontal bias of ϩ12 and parietal/frontal bias of ϩ25 BIS units. 20 This is in accordance with our study results of a consistent occipital/frontal bias of ϩ10 BIS units. They also found weak frontal-central correlation (r 2 ϭ 0.374) and moderate frontal-parietal correlation (r 2 ϭ 0.66), 20 which was also comparable with our moderate frontal/occipital correlation (r 2 ϭ 0.671) during anesthesia maintenance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Secondly, it is possible that discrepancies in the predictive ability of the Marsh pharmacokinetic model for plasma propofol may compromise the study. However, previous studies have not demonstrated systematic inaccuracies in the Marsh model in a patient population comparable to our study group [15]. Moreover, the sequences of changes in EtCO 2 were randomised and would have negated inaccuracies created by the Marsh model.…”
Section: Discussionmentioning
confidence: 67%
“…The complexity of the CNS lies probably not only in its structural complexity but also in its spatial and temporal metabolic and functional variability in either awake or comatose/unconscious patients, under anesthesia or in ICU [18]- [25]. To take that into account, neuro-monitoring has not to be too excessively simplified [26]- [28] and limited only to the forehead, as accurately described by John in his "anaesthetic cascade" [19].…”
Section: Temporal Topographical and Spatial Variations: The Brain Mmentioning
confidence: 99%